An Instrumental Theory of Political Correctness - Stephen Morris (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
An informed advisor wishes to convey her valuable information to an uninformed decision maker with identical preferences. Thus she has a current incentive to truthfully reveal her information. But if the decision maker thinks the advisor might be biased in favor of one decision, and the advisor does not wish to be thought to be biased, the advisor has a reputational incentive to lie. I show that if the advisor is sufficiently concerned about her reputation, no information is conveyed in equilibrium. I also show that in a repeated version of this game, the advisor will care (instrumentally) about her reputation simply because she wants her valuable and unbiased advice to have an impact on future decisions.
Keywords: 330